Internalisasi Nilai-Nilai Fikih dalam Kitab Fath Al-Qorib - Hasan, Sholeh (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2019)
Internalization of values ​​in forming a desired character certainly requires a well-planned process. Can be through individual, group and institutional relationships. Darul Ihya Islamic Boarding School as a non-formal educational institution is expected to give a role in shaping human beings with Islamic characteristics. In this pesantren the author makes the media devotion in order to internalize the values ​​of fiqh in the book Fath Al-Qorib. By using the bandongan method, a group of students in one class listens to an ustadz who reads, translates, explains the material contained in the book Fath al-Qorib. Each santri pays attention to his book and makes notes about difficult words or thoughts, in the form of saffron or mufrodat meanings. The learning of the yellow book which had been carried out in the Darul Ihya Islamic boarding school had considerable implications for the formation of Islamic character for the santri. So that the presence of writers besides being able to meet the shortcomings of human resources experienced by the Darul Ihya Islamic boarding school can also contribute in carrying out the programs launched by the pesantren.